CORRELATION BETWEEN BLOOD GLUCOSE LEVEL AND BODY MASS INDEX AMONG PREGNANT WOMEN WITH EXCESS BODY WEIGHT - Surbakti, Betharia Lorenza Br; Amansyah, Adek; Lina, Juliana (Universitas Tadulako, 2021)
Amount of 207 million (83.6%) women who give birth simultaneously are diagnosed with GDM in 2019. Prevalence of GDM reaches 1.9-3.6% in Indonesia. Amount of 40-60% of GDM will suffer from postpartum Non-Dependent Insulin Diabetes Mellitus. Hence, this study was aimed to look for the distribution of blood sugar levels among pregnant women who are overweight. This research was performed among pregnant women in the Obstetrics and Gynecology polyclinic of Royal Prima Medan Hospital against 41 people as the sample with a cross-sectional model (Longitudinal study). The aspects evaluated in this study were age, gestational age, BMI, occupation, income, recent education, history of gestational DM, Macrosomia, and obstetrics. All research data was analyzed with SPSS 25 by spearman correlation. The trend of random et blood sugar levels of pregnant women as respondents was 100 mg/dL, while the BMI tendency was 31.72 kg/m2. Based on these parameters, they had a correlation with each other among overweight pregnant women (Value P = 0.007) that was moderate (R = 0.417). Blood sugar levels were moderate correlated with BMI among pregnant women with excess body weight.